Photoinduced synthesis and antitumor activity of a phakellistatin 18 analog with an isoindolinone fragment. (4th November 2020) - Bao, Yujun; Jiang, Shitian; Zhao, Lishuang; Jin, Yingxue; Yan, Rui; Wang, Zhiqiang
Abstract : Photoinduced synthesis and antitumor activity of a phakellistatin 18 analog with an isoindolinone fragment. Abstract : Cyclic peptides have become a powerful modality in drug development. Naturally isolated cyclic peptides such as phakellistatins have been found to have broad-spectrum bioactivity. In this paper, we have prepared an analog of phakellistatin 18, and tried to compare its bioactivity with that of our reported phakellistatin 2 analog. It was found that compound 1 derived from phakellistatin 18 showed inferior inhibiting ability compared to the phakellistatin 2 analog, similar to the phenomenon observed in the natural products (phakellistatin 2 presented stronger antitumor activity than that of phakellistatin18). We have performed molecular docking of the two analogs with the MDM2 protein using AutoDock Tools, which showed that the phakellistatin 2 analog presented stronger binding through a H-bond, providing an explanation for the bioactivity difference.